Socio –Economic Interaction of Sota-PNG Cross_Border Community - Fitriani, Fitriani; Laode, Imelda C.; Sukardi, Sukardi (Technium Social Sciences Journal, 2023)
The purpose of this research is to find the form of socio-economic interaction of Sota - PNG border crossers in this case is Kle Kanume who settled in the territory of the Republic of Indonesia and the territory of Papua New Guiene. The method used is a qualitative method with a descriptive approach combined with interviews and observations. This research was conducted in Sota District, Sota Village, Merauke Regency, South Papua. The focus of this research is the local community of Sota-PNG border crossers, namely the Kanume Tribe/Klen. The reason for choosing this research focus is because some Klen Kanume are residents who inhabit the Sota Village of Sota District and some Klen Kanume inhabit the Morhead District of PNG. The results of this study found that this border crossing community is an actor who daily crosses the Sota-PNG border to conduct socio-economic interactions with various purposes (Socio-Cultural, Economic, Health, and Education).